Research on Material Forming and Control Engineering Optimization Based on Computational Intelligence - Liu, Xiaoyan (2023 International Conference on Mechatronics, IoT and Industrial Informatics (ICMIII), 2023)
With the rapid development of science and technology, electronic technology and materials science have also gained a very broad development prospect, and the research on various intelligent things, such as smart phones, smart TVs and intelligent control systems, has been deepened. Intelligent materials are also products of intelligence. Intelligent materials are a new type of materials in the 21st century. The inspiration of intelligent materials comes from bionics, which is the direction of material science development. In the process of engineering construction, engineering materials are also developing rapidly in the direction of intelligence. Nowadays, the application of intelligent materials is more and more extensive. As a new material category in modern times, intelligent materials have an absolute advantage in terms of quality and use. In this paper, the subject of engineering control optimization is discussed in detail in combination with the molding of intelligent materials.